Sistem Pendukung Keputusan Pemilihan Tanaman Pertanian Berdasarkan Kondisi Lahan dan Iklim Menggunakan Metode AHP-TOPSIS - Ikhwanuddin, Yazid; Suharjo, Imam (Journal of Informatics Management and Information Technology, 2026)
The selection of crops that are suitable for land and climate conditions is an important factor in increasing agricultural productivity and resource utilization efficiency. This study aims to develop a decision support system (DSS) in the selection of food and horticultural crops based on local agroclimatic conditions using an integration of the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The case study was conducted in Bantul Regency, Yogyakarta Special Region, by considering five main criteria, namely soil type, humidity, rainfall, air temperature, and altitude, as well as five alternative crops, namely rice, corn, soybeans, tomatoes, and chilies. The AHP method was used to determine the importance weight of each criterion based on expert assessment, while the TOPSIS method was used to rank alternative crops based on their suitability level. The results of the AHP calculation showed that soil type was the most influential criterion with a weight of 0.4301, followed by humidity, rainfall, altitude, and air temperature. Based on the TOPSIS analysis, rice plants obtained the highest preference value (C = 0.8688), so it is recommended as the most suitable plant for the agro-climatic conditions of Bantul Regency, while chili plants obtained the lowest preference value (C = 0.1311). These ranking results are in line with the real conditions and historical agricultural patterns in Bantul Regency, which is known as one of the rice production centers, thus indicating that the proposed DSS model is able to represent the agro-climatic conditions of the study area rationally and based on data. This research is expected to be the basis for the development of a more adaptive and applicable agricultural decision support system in supporting crop cultivation planning.